UK Ocean Acidification programme D366 cruise around the British Isles CTD bottle sample measurements. - Ribas Ribas, Mariana; Achterberg, Eric P; Archer, Steve; Bakker, Dorothee; Clark, Darren; Hopkins, Frances E; Moore, C Mark; Lawson, Hannah E; Lee, Gareth; Palmer, Matthew; Poulton, Alex; Richier, Sophie; et al. (British Oceanographic Data Centre, Natural Environment Research Council, 2014)
This dataset is a synthesis of the CTD measurements made on station samples collected on RRS Discovery cruise D366. The cruise was the first of three cruises undertaken by the Sea Surface consortium of the UK Ocean Acidification (UKOA) programme. The cruise took place in the northwestern European shelf seas around the British Isles during June and July 2011. Participants from UoS, NOCS, UEA, UCL, UoE and PML between them measured two independent carbonate chemistry variables (TA and DIC); chlorophyll and size fractionated chlorophyll; particulate organic phosphorous, carbon and nitrate; transparent exoploymer particles, dissolved organic carbon, total dissolved nitrogen; dimethylsulphide and Dimethylsulfoniopropionate; ammonium; ammonium regeneration, oxidation and assimilation; NO2 oxidation and assimilation; NO3 assimilation; cocolithophores, diatoms and microzooplankton counts; biogenic silica; and inorganic nutrients from 69 stations during the cruise. Samples were collected from the CTD at different depths. During or after the cruise the analyses for each measurement followed the standard protocols detailed with the dataset. After the cruise the data were aggregated for a complete quality control and some additional parameters were derived (DON, additional carbonate chemistry parameters). Calibrated salinity, dissolved oxygen and temperature from the CTD system as processed by NOCL are included as ancillary data. The collection of these data and the subsequent synthesis were funded as part of the UKOA programme by NERC, DEFRA and DECC.